2015
DOI: 10.18488/journal.1/2015.5.5/1.5.298.308
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Sustainable Competitive Advantage Model Based On Balanced Scorecard

Abstract: Nowadays organizations turn to any standard procedure to gain a competitive advantage. If sustainable, competitive advantage can bring about benefit to the organization. The aim of the present study was to introduce competitive advantage as well as to assess the impacts of the balanced scorecard as a means to measure the performance of organizations. The population under study included employees of organizations affiliated to the Social Security Department in North Khorasan Province, of whom a total number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 22 publications
3
36
0
3
Order By: Relevance
“…Also, the second hypothesis which states that there is no significant relationship between competitor's sales data and business competitive advantage, the study found out that competitor's sales data is significantly related to business competitive advantage. This result is line with the findings of Hakkak and Ghodsi (2015) which indicated that there is a significant and positive impact of the implementation of the competitors' sales record and balanced scorecard on the sustainable competitive advantage.…”
Section: Discussion Of Findingssupporting
confidence: 91%
See 1 more Smart Citation
“…Also, the second hypothesis which states that there is no significant relationship between competitor's sales data and business competitive advantage, the study found out that competitor's sales data is significantly related to business competitive advantage. This result is line with the findings of Hakkak and Ghodsi (2015) which indicated that there is a significant and positive impact of the implementation of the competitors' sales record and balanced scorecard on the sustainable competitive advantage.…”
Section: Discussion Of Findingssupporting
confidence: 91%
“…The impact of competition in the business environment has compelled many organizations to turn around and start scanning the environment for information, so as to have competitive edge over other similar organization within the industry. Hakkak and Ghodsi (2015) in their research conducted to introduce competitive advantage as well as to assess the impacts of the balanced scorecard as a means to measure the performance of organizations. 120 employees of the organizations affiliated to the social security department in North Khorasan Province were selected as the participants in the research.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Despite all that, Porter did not provide a definition of sustainable competitive advantage. In 1991, Barney introduced the closest definition of sustainable competitive advantage such as the continuity in benefits and applying strategies that create unique value where other competitors cannot imitate as it becomes unique and exclusive to the company [25]. Dickson (1992) and Hamel and Prahalad (1989) discussed how companies need to create new merits that keep them in the front and advance in comparison with other competing companies and also to search for ways for distinction [26].…”
Section: Sustainable Competitive Advantagementioning
confidence: 99%
“…In spite of the fact that the particular issues announced identifying with the Italian setting, it tends to have contended that they are sensibly illustrative of most Western markets. Furthermore, [14] demonstrate the information examination was performed utilizing the basic condition displaying and the outcomes showed the noteworthy and positive effect of the usage of the balanced scorecard on the sustainable in telecommunication industry…”
Section: Strategic Planningmentioning
confidence: 99%